The activities of the Lithuanian working people in creating the material basis of schools in the period of construction of socialism - Gruzdys , V. (Psichologija, 1969)
When Soviet Lithuania was liberated from the German invaders, together with the restoration and development of the national economy popular education was in the centre of attention of the Lithuanian Communist party and the Soviet Government. A successful development of the national economy and a constant support of our sister republics made it possible to increase the assignations to popular education every year. The assigned sums let us successfully put into life the undertaken task by our Party - compulsory seven-year education - and create conditions for passing on to universal secondary education. The best necessary conditions were made for a normal educational work at schools. They were provided with premises and school supplies. Teachers, workers ant youth showed a great initiative and patriotism. Thanks to them in our republic a new way of building schools began spreading. Hundreds of schools for tens of thousands of working places were reconstructed and built. Sister republics gave a great help in restoring schools and developing their material basis.
Keywords: history of pedagogy; creation of material basis